Preparation, formation mechanism and in vitro dynamic digestion behavior of quercetin-loaded liposomes in hydrogels. (July 2020) - Liu, Weilin; Kong, Youyu; Ye, Aiqian; Shen, Ping; Dong, Lu; Xu, Xiankang; Hou, Yingying; Wang, Yanping; Jin, Yangyi; Han, Jianzhong
Abstract: Quercetin-loaded liposomes in hydrogels (lipogels) with different texture properties were fabricated, and their formation mechanism, along with the in vitro oral-gastrointestinal fate, were investigated. The hydrogels, composed of chitosan and gelatin, were cross-linked by ionic and covalent bonds, and interacted with liposomes by hydrogen bonds. More fragmentations were obtained from hard lipogels than soft lipogels after simulated oral processing. In the self-developed artificial gastric digestive system and small intestinal compartment, higher level of breakdown and more release of liposomes and quercetin occurred in the soft lipogels. Besides, compared to the liposomes without embedding in hydrogels, the lipogels showed better protective effect of quercetin from gastric release by ~40%. The results showed that the texture and structure played key roles in the lipogels degradation and cargo release during digestion, thus illustrating a considerable approach to control the release of functional molecules and the potential application of the lipogels as a bio-food. Graphical abstract: Image 1 Highlights: Soft and hard quercetin-loaded liposomes in hydrogels (lipogels) were fabricated. Hydrogel formed by ionic and covalent bond, and interacted with liposome by H-bond. A self-developed gastric and small intestinal system was used for dynamic digestion. More breakdown and cargos release were from soft than hard lipogel in GIT model. Lipogels showed better protection of quercetin than liposomes in simulated stomach.